Fitness effects and transmission routes of a microsporidian parasite infecting Drosophila and its parasitoids. - Futerman, P; Layen, S; Kotzen, M; Franzen, C; Kraaijeveld, A; Godfray, H (2006)
A microsporidian infection was discovered in laboratory cultures of Drosophila species. Ultrastructural examination suggested it belonged to the poorly characterized species Tubulinosema kingi, and morphological and sequence data are presented. We explored how T. kingi affected the fitness of Drosophila melanogaster and D. subobscura, as well as the fitness of 2 of their parasitoids, Asobara tabida and Pachycrepoideus vindemiae. In Drosophila, infections caused changes in most of the traits we looked at that were associated with fitness, in particular causing a 34-55% reduction in early-life fecundity. Parasitoid fitness was affected more severely by infection than that of their hosts, with pupal mortality in particular increasing by 75-89%. We investigated the most important routes of transmission for T. kingi in a laboratory setting. Letting Drosophila larvae feed on medium contaminated with spores from infected dead flies resulted in 100% infection. Low levels of transmission (<10%) were found between larvae, and vertically between mothers and their offspring. Parasitoids developing in infected hosts all became infected, but infected adults were neither able to transmit the pathogen to their offspring nor to their offspring's Drosophila host, either directly, or via contamination of the ovipositor or other body parts. A field survey of Drosophila and their parasitoids in southern England revealed no natural infections. We discuss the potential importance of Microsporidia in parasitoid-host interactions, and for those working with Drosophila in the laboratory.